Biosafety challenges and the future landscape in Pakistan - Akhtar Sherin (Khyber Medical University Journal, 2024)
Sepsis is a major threat to global health, as highlighted by the Global Burden of Disease Study, which recorded an estimated 48.9 million cases of sepsis globally, resulting in 11.0 million sepsis-related deaths, accounting for 19.7% of all global deaths in 2017. The incidence and mortality rates of sepsis are particularly high in sub-Saharan Africa, Oceania and South Asia.1 In developing countries, the increasing incidence of sepsis poses a significant challenge, emphasizing the imperative need to prioritize biosafety measures for public health protection. Ensuring biosafety is crucial for the safe handling of biological materials, safeguarding researchers, laboratory personnel, animals and the environment from infectious agents and toxins. In Pakistan, this critical need highlights the urgent requirement for robust biosafety frameworks, where establishing and maintaining these practices remains a formidable challenge.2